2012
DOI: 10.1186/1471-2164-13-710
|View full text |Cite
|
Sign up to set email alerts
|

The arthritis severity locus Cia5a regulates the expression of inflammatory mediators including Syk pathway genes and proteases in pristane-induced arthritis

Abstract: BackgroundCia5a is a locus on rat chromosome 10 that regulates disease severity and joint damage in two models of rheumatoid arthritis, collagen- and pristane-induced arthritis (PIA). In this study, we aimed to identify cellular and molecular processes regulated by Cia5a using microarray-based gene expression analysis of synovial tissues from MHC identical DA (severe erosive disease) and DA.F344(Cia5a) congenics (mild non-erosive disease) rats.ResultsSynovial tissues from six DA and eight DA.F344(Cia5a) rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Thus, tissue and cellular damage that occurs under both infected and sterile conditions can induce the activation of NF- κ B and AP-1 via pattern recognition receptors such as TLRs in a similar manner [ 58 ]. Previous reports [ 60 62 ] and our data strongly indicate that the activation of Src, Syk, IRAK1, and IRAK4 is present in both in vitro and in vivo inflammatory models (Figures 3 and 4 , data not shown). In addition, KF strongly inhibits the phosphorylation and subsequent enzyme activity of Src, Syk, IRAK1, and IRAK4, which is linked to its anti-inflammatory action (Figures 3 and 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, tissue and cellular damage that occurs under both infected and sterile conditions can induce the activation of NF- κ B and AP-1 via pattern recognition receptors such as TLRs in a similar manner [ 58 ]. Previous reports [ 60 62 ] and our data strongly indicate that the activation of Src, Syk, IRAK1, and IRAK4 is present in both in vitro and in vivo inflammatory models (Figures 3 and 4 , data not shown). In addition, KF strongly inhibits the phosphorylation and subsequent enzyme activity of Src, Syk, IRAK1, and IRAK4, which is linked to its anti-inflammatory action (Figures 3 and 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…Xue et al (24) reported that endogenous MMP-9 contributes to prolonged survival and invasive and inflammatory properties of RASFs. While MMP-9 is able to degrade the extracellular matrix, it is also implicated in the development of cartilage and bone erosion in RA (25). A previous study by Perisic et al (26) demonstrated that PCSK6 mRNA expression levels are positively correlated with typical markers of inflammation and apoptosis, including IL-1β and TNF-α, and proteins involved in matrix degradation, such as MMP-9, in vascular disease.…”
Section: Discussionmentioning
confidence: 97%
“…We observed similar results with R406 in the human RA-derived synoviocyte cell line MH7A (see text). Moreover, Syk pathway genes are upregulated in synovial tissues from CIA-susceptible rodents when compared to CIA-resistant congenic controls [ 47 ]. In the context of lupus, T-cells from a subset of patients display aberrant signaling due to abnormal recruitment of Syk to the T-cell receptor (TCR) complex.…”
Section: Discussionmentioning
confidence: 99%